Advertising & promotion - Hackley, Chris; Hackley, Rungpaka Amy (Los Angeles : SAGE, 2021)
'Now in its fifth edition, this popular textbook continues to provide students with a comprehensive insight into the world of advertising and promotional communications. Unique in its approach, the authors situate the key concepts of marketing communications from the perspective of advertising agencies and provide insight into what a career within an ad agency might be like. Their critical approach grounded in up-to-date research allows the reader to develop an interdisciplinary understanding of marketing and advertising, including business, socio-cultural, media studies and consumer culture theory perspectives. Along with striking full colour visual advertisements and illustrations, new examples and case studies, this fifth edition has been fully updated to include: two brand new chapters on Social Media Advertising and Digital Advertising; commentary on how the COVID-19 pandemic has and will impact advertising; the evolving role of advertising agencies in the post digital era; and emerging forms of advertising and promotion, including the role of influencers.' --Provided by publisher.
Includes bibliographical references:(pages 374-395) and index.
Keywords: Advertising; Advertising -- Social aspects; Sales promotion; Advertising -- Brand name products